The Main Benefits of Application of Six Sigma for Productive Excellence - Gomes, Fabricia da Silva; Camargo, Paulo R.; da Motta Reis, José S.; Diogo, Gabriel M. M. [UNESP]; Cardoso, Ronald P.; de Barros, José G. Medeiros; de Souza Sampaio, Nilo A.; Barbosa, Luís C. F. M.; Santos, Gilberto (Technical University of Kosice, 2022)
Purpose: The present paper addressed the application of the Six Sigma method for process management to reduce the variability and scrap of packages manufactured at a company located in the city of Rio de Janeiro. Methodology/Approach: Exploratory research was conducted to understand the context, analyse, and create familiarity with the problems identified in the company, making them more explicit. Findings: Through Define, Measure, Analyze, Improve, Control (DMAIC) the company was able to identify the main causes of customer complaints and the factors that led to these complaints. Using management tools, it was possible to solve the problems with packaging outside the specifications, which was the reason for complaints from customers. The benefits of this research were the identification and analysis of the quality management tools. Research Limitation/Implication: The present research had as a limitation the application of the method is only one company, so it is proposed as a future study of the application in different production processes of different organizations. Originality/Value of paper: It was evidenced that there is a positive relationship between the application of Quality management methods and company billing, as there was an increase of 1.7% in company billing. In past surveys, new possibilities for improvement to be addressed emerged, making the team aware of the need to continue the process of continuous improvement. Category: Research paper.
Keywords: quality management; quality tools; six sigma; total quality management